Defect analysis and lean six sigma implementation experience in an automotive assembly line. (2020) - Krishna Priya, S.; Jayakumar, V.; Suresh Kumar, S.
Abstract: This paper presents a case study on implementation of lean six sigma in an automotive assembly plant in order to reduce/eliminate non-value added processes in the assembly line. A thorough defect analysis is carried out in the automotive assembly plant to examine, measure and reduce sources of flaws in an operational process in question, to optimize the defect occurrence, improve and sustain performance throughout the automotive assembly process. In the automotive assembly division considered for study, three non-value added activities and 12 crucial defects were identified and the potential solutions were provided using lean six sigma strategies like DMAIC (Define–Measure-Analyze-Improve-Control) & RCA (Root Cause Analysis) tools and techniques. The implementation of proposed solutions have resulted in drastic reduction of non-value added processes and defect ratio in the assembly line.